"Quit Ditching the Love": Kinship and Death from Opioid Overdose in Philadelphia. Issue 1 (7th November 2021) - Uzwiak, Beth A.
Abstract: In 2017, 1, 074 persons died from opioid overdose in Philadelphia; more than 78% of those happened in a private residence. Despite constituting the majority of opioid‐related deaths in the city, little is known about people who use opioids, overdose, and die while at home. To learn more about this "hidden" population of drug users, researchers conducted exploratory, in‐depth qualitative interviews with their next of kin. Collected in the context of death, I discuss data from the interviews to consider how and if representing pain contributes to interventions aimed at reducing structural vulnerability to drug overdose. I suggest that documenting and taking seriously next of kin's experiences with death and the threat of death can substantiate the need for harm reduction programs and policy, corroborating the utility of qualitative approaches to applied health research.